Pekanbaru Cineplex Dengan Pendekatan Arsitektur Post-Modern - Annisa Cinintya; Muhammad Rijal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Cinema is one of alternatives for recreation, watching movies in cinema become a hobby and a lifestyle for some people. Therefore the necessity of cinema becomes important for citizen in Pekanbaru .The design of cinema in this paper is using “Asymmetrical Symmetry” concept, the display forms a balanced of asymmetries that transformed into the building. In term of cinema building design, post-modern architecture is seen as the most suitable and attractive for the building. In addition, not merely the appearance and the shaped, the cinema needs to pay attention on convenience of the users of the building. The final results of the application is implemented in the design of a cinema which includes zoning, mass form, outdoor layout, inner space, and the building's facade. In the mass formations, the concept transformed to building height difference and axis line which one divides the building mass. Facade on two sides of the building is made different and contrast.Keyword: Cineplex, Cinema, Post-modern Architecture, Asymmetrical Symmetry